Synthesis and physicochemical studies of new aminalkyl derivatives of succinimide with potential anticonvulsant activity - Rybka, Sabina (2017)
In the introduction of the doctoral thesis, different ways of searching for new anticonvulsants were described. New drugs obtained as a result of modifications of antiepileptic drugs and some examples of drugs with new structures which are different from the known antiepileptic drugs were also presented.The aim of the work was to obtain series of pyrrolidine-2,5-dione derivatives containing various moieties at position-3, and 4-substituted piperazine, piperidine or morpholine linked to imidazole atom by various length of alkylene chains, with potential anticonvulsant activity.In the experimental section, the synthesis of planned derivatives was described. As a result, 132 compounds were obtained. The structures of synthesized compounds were confirmed by elemental analysis and 1H-NMR, 13C-NMR, 19F-NMR and LC/MS spectra, whereas purity and homogeneity by chromatographic methods.Anticonvulsant activity was examined using MES, scPTZ and 6 Hz tests. Based on these results, the structure-activity relationship was determined. In addition, the probable mechanism of action was identified for the most active compounds, and it was associated with the blocking of sodium channels and/or calcium L-channels.Moreover, lipophilicity was determined for selected derivatives, and the lipophilicity-activity relationship was established, as well. Metabolism of selected compounds was also tested.
Keywords: anticonvulsant activity; succinimide; pyrrolidine-2; 5-dione